Pengaruh Pemberian Ekstrak Biji Bengkuang (Pachyrhizus erosus L.) Terhadap Hama Ulat Grayak (Spodoptera litura) Pada Tanaman Sawi - Muhammad Mijan Gulam; Helda Orbani Rosa; Yusriadi Marsuni (JURNAL PROTEKSI TANAMAN TROPIKA, 2023)
Research has been carried out on the use of botanical pesticides from yam seed extract against Spodoptera litura larvae. The aim was to determine the effect of yam bean seed extract as a natural pesticide on the mortality of armyworm pests and reduce the intensity of attacks on mustard greens. This study used one factor RAL with 6 treatments and 4 replications, as a control with two ingredients, namely chemical pesticides and water. Observation of mortality was observed every 6 hours for 3 days in the laboratory and observation of attack intensity for 7 days in the greenhouse. In each treatment, 10 S. litura larvae were invested so that in the experimental unit there were 240 larvae tested both for mortality and attack intensity. The results of the research on Jicama seed extract showed the highest percentage of mortality at a concentration of 15% of 37.5%, while the lowest percentage of attack intensity was at a concentration of 15% of 87.9%.